Tradisi Sayyang Pattudu di Mandar (Studi Kasus Desa Lapeo) - Ruhiyat, Ruhiyat (Jurnal Studi Agama dan Masyarakat, 2017)
In the sociological view, Mandarese believes that Sayyang Pattuâduâ tradition has a close affinity with each other. As a reason, Pattuduâ Sayyang tradition was held in order to appreciate the children who have finished readying all the content of their Al-Qurâan. For the resident of Mandar especially in Lapeo village, the Tradition of Sayyang Pattuduâ meant as a socialization tool because involve the resident inÂ  an effort toÂ  achieve a Â goal together. Â InÂ  addition, this tradition can also increase the integration and strengthen the solidarity process among the resident. It was unquestionable if in the midst of this traditionâs process some of the various groups of people take advantages from this moment on their behalf. Therefore, the problems appears in this research are how the image of the interaction and social dynamic within the tradition of Sayyang Pattuduâ and to what extent the resident of Lapeo village interpret Sayyang Pattuduâ tradition.